Optimization of ocean thermal energy conversion based on pressure energy recovery of ammonia water working medium - Mingqian Tian; Yanni Yu; Yunxing Hou; Yun Chen; Li Zhang; Yanjun Liu; Yanjun Liu (Frontiers in Energy Research)
Ocean thermal energy conversion is a new energy technology that utilizes the temperature difference conditions of seawater to generate electricity. This paper focuses on the closed cycle of ocean thermal energy conversion using ammonia as the working fluid. Based on pressure energy utilization devices such as pressure exchangers, hydraulic turbines, and ejectors, three methods are proposed to recover and utilize the pressure energy of the lean ammonia solution, in order to improve the thermal efficiency and systematic performance. By analyzing and comparing the performance of the cycle, it can be concluded that all three methods can achieve a utilization of pressure energy, and under the same conditions, the highest thermal efficiency of the ejector cycle is 5.71%.